2014
DOI: 10.1007/s00167-014-3261-5
|View full text |Cite
|
Sign up to set email alerts
|

Predictive parameters for return to pre-injury level of sport 6 months following anterior cruciate ligament reconstruction surgery

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
147
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(161 citation statements)
references
References 48 publications
9
147
3
2
Order By: Relevance
“…Pietrosimone et al 4 observed larger correlations (r ¼ 0.78) and stronger predictability (R 2 ¼ 0.61) between strength and IKDC scores in patients who had undergone ACL-R. Their ACL-R cohort reported levels of disability (IKDC score ¼ 86.1 6 8.9) and postoperative time (4.5 6 3.4 years) similar to those in our study; yet their peak torque values (2.73 6 0.57 Nm) were higher and their sample size (n ¼ 15) was smaller. 4 Multiple variables may contribute to subjective knee function after ACL-R, including psychological factors, 31 surgical technique, 32 associated knee damage, 33 activity demands, 34 and overall health of the patient. 35 The results of our predictive model indicated that as months after surgery increased (ranging from 6 to 107 months [8.9 years]), subjective knee function increased.…”
Section: Discussionmentioning
confidence: 99%
“…Pietrosimone et al 4 observed larger correlations (r ¼ 0.78) and stronger predictability (R 2 ¼ 0.61) between strength and IKDC scores in patients who had undergone ACL-R. Their ACL-R cohort reported levels of disability (IKDC score ¼ 86.1 6 8.9) and postoperative time (4.5 6 3.4 years) similar to those in our study; yet their peak torque values (2.73 6 0.57 Nm) were higher and their sample size (n ¼ 15) was smaller. 4 Multiple variables may contribute to subjective knee function after ACL-R, including psychological factors, 31 surgical technique, 32 associated knee damage, 33 activity demands, 34 and overall health of the patient. 35 The results of our predictive model indicated that as months after surgery increased (ranging from 6 to 107 months [8.9 years]), subjective knee function increased.…”
Section: Discussionmentioning
confidence: 99%
“…The ACL-RSI was shown to help to identify patients who return to sport and who do not (10). Muller et al showed that ACL-RSI scale was the strongest predictive parameter of RTS at 6 months following ACLR (14). It was suggested that addressing the patients' fear of re-injury during early phase of the postoperative rehabilitation might decrease its impact on knee functions (15).…”
Section: Introductionmentioning
confidence: 99%
“…71 Although patient-reported outcomes provide valuable information about strength and functional performance, 2,64,119,137,208 time from surgery remains the only criterion to return someone to unrestricted activity. 16 Most patients are returned to sport between 6-8 months after reconstruction, 16 which is concerning given the decreased quadriceps strength, quadriceps activation, and functional performance during this time period.…”
Section: Return To Activity Assessmentsmentioning
confidence: 99%
“…16 Most patients are returned to sport between 6-8 months after reconstruction, 16 which is concerning given the decreased quadriceps strength, quadriceps activation, and functional performance during this time period. 47,73,137,141,175,191,192 Even quadriceps strength deficits around 15%…”
Section: Return To Activity Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation